Molecular Approach to Microbiological Examination of Water Quality in the Grand Bay National Estuarine Research Reserve (NERR) in Mississippi, USA - Stephen S. Kishinhi; Paul B. Tchounwou; Ibrahim O. Farah (SAGE Publishing, 2013)
Grand Bay National Estuarine Research Reserve (NERR) is an important ecosystem in the Mississippi Gulf Coast. It serves as important nursery areas for juveniles of many species of fish. The bay is also used for fishing, crabbing, oyster togging, boating as well as recreation. Like in other aquatic environments, this bay may be contaminated by microorganisms including pathogenic bacteria. The objective of this study was to evaluate the microbiological quality of water in the Grand Bay NERR and determine the levels and potential source(s) of human fecal pollution. To achieve this goal, water samples were collected aseptically every month in Bayou Heron, Bayou Cumbest, Point Aux Chenes Bay and Bangs Lake. Enterococci were concentrated from water samples by membrane filtration according to the methodology outlined in USEPA Method 1600. After incubation, DNA was extracted from bacteria colonies on the membrane filters by using QIAamp DNA extraction kit. Water samples were also tested for the presence of traditional indicator bacteria including: heterotrophic plate count, total coliforms, fecal coliforms, and Enterococcus bacteria. The marker esp gene was detected in one site of Bayou Cumbest, an area where human populations reside. Data from this study indicates higher concentrations of indicator bacteria compared to the recommended acceptable levels. Presence of esp marker and high numbers of indicator bacteria suggest a public health concern for shellfish and water contact activities. Hence, control strategies should be developed and implemented to prevent further contamination of the Grand bay NERR waters.